Design and Development of a Shortwave near Infrared Spectroscopy using NIR LEDs and Regression Model - Kim Seng Chia; Yit Peng Tan (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Near infrared (NIR) spectroscopic technology has been getting more attention in various fields. The development of a low cost NIR spectroscopy is crucial to reduce the financial barriers so that more NIR spectroscopic applications will be investigated and developed by means of the NIR spectroscopic technology. This study proposes an alternative to measure shortwave NIR spectrum using one collimating lens, two slits, one NIR transmission grating, one linear array sensor, and one microcontroller. Five high precision narrow bands NIR light emitting diodes (LEDs) were used to calibrate the proposed spectroscopy. The effects of the proposed two slits design, the distance between the grating and linear array sensor, and three different regression models were investigated. The accuracy of the proposed design was cross-validated using leave-one-out cross-validation. Results show that the proposed two slits design was able to eliminate unwanted signals substantially, and the cross-validation was able to estimate the best model with root mean squared error of cross-validation of 3.8932nm. Findings indicate that the cross-validation approach is a good approach to estimate the final model without over-fitting, and the proposed shortwave NIR spectroscopy was able to estimate the peak value of the acquired spectrum from NIR LEDs with RMSE of 1.1616nm.